1996
DOI: 10.1002/(sici)1096-987x(199605)17:7<806::aid-jcc5>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Extension of MST/SCRF method to organic solvents:Ab initio and semiempirical parametrization for neutral solutes in CCl4

Abstract: The self‐consistent reaction field (SCRF) method proposed by Miertus, Scrocco, and Tomasi (MST) was extended to solutions of neutral solutes in CCl4. A detailed parametrization of the solute/solvent interface and of the “hardness” atomic parameters determining the van der Waals interactions was performed from comparison with experimental data and Monte Carlo simulations. The parametrization was carried out at both ab initio (6‐31G*) and semiempirical (MNDO, AM1, PM3) levels. The MST/SCRF optimized versions pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 87 publications
(2 reference statements)
3
98
0
1
Order By: Relevance
“…Finally, DG vW is computed using a linear relationship to the solvent-exposed surface of each atom (Eq. 5) [20][21][22][23][24], where the atomic surface tensions are determined by fitting to a set of experimental free energies of solvation…”
Section: Ief-mst Modelmentioning
confidence: 99%
“…Finally, DG vW is computed using a linear relationship to the solvent-exposed surface of each atom (Eq. 5) [20][21][22][23][24], where the atomic surface tensions are determined by fitting to a set of experimental free energies of solvation…”
Section: Ief-mst Modelmentioning
confidence: 99%
“…The gas phase optimized geometries were used in the liquid phase calculations without any corrections. It has been noted that the use of gas phase geometries in the calculations for the solvation process does not introduce significant errors when compared to geometries optimized in solution [25].…”
Section: Parameterization Proceduresmentioning
confidence: 99%
“…Generally, this scaling factor is chosen by maximizing the agreement between experimental data and computed values of some property for a representative group of solutes in a given solvent. Several parameterizations of the PCM, which make directly use of atomic radii and a suitable scaling factor, are described in the literature for the solvation processes of neutral molecules in water [16] and organic solvents such as chloroform [24], carbon tetrachloride [25], and octanol [26].…”
Section: Introductionmentioning
confidence: 99%
“…34,35 The problem is shifted to the size of the spheres, and several studies have shown that standard van der Waals radii provide reasonable cavity sizes. 36 This situation results in difficulties for the continuum model to represent some apolar solvents, e.g. cyclohexane.…”
Section: Shield Tensor Calculation: S-md/qm Methodologymentioning
confidence: 99%